Training Teachers of History at Sakhalin State University: Historical Experience of 1949–2024 - Natalia V. Potapova (СибСкрипт, 2025)
Although historical education is now a national priority, the regional experience of its development on the island of Sakhalin remains understudied. The Yuzhno-Sakhalinsk State Institute of Teachers’ Training was the first higher education institution on Sakhalin. Eventually, it became the Yuzhno-Sakhalinsk State Pedagogical Institute, which, in its turn, was transformed into the Sakhalin State University. The article traces its experience in training history teachers. Based on the concept of modernization as part of higher education reforms, the author analyzed regulatory legal acts and documents stored in regional, departmental, industrial, and personal archives. The research yielded a periodization of the 75-year history of historical and pedagogical education in the Sakhalin Region, based on modernization processes, social transformations, and state reforms in the field of higher education. The peculiarities, problems, and prospects for the historical and pedagogical education in the Sakhalin Region depend on its status as a sparsely populated frontier territory of resource nature. These factors triggered a strong outmigration in the early 1990s. The recent reforms of the higher education system also caused major damage to the local university and historical faculty members. However, the growing prestige of historical and pedagogical education may yet improve the state of affairs for the local academia and school teachers.